Endoplasmic reticulum stress occurs in association with the extrusion of toxic extracellular vesicles from human placentae treated with antiphospholipid antibodies. Issue 5 (4th March 2020) - Tang, Yunhui; Chen, Yan; Nursalim, Yohanes; Groom, Katie; Hickey, Anthony; Chamley, Larry; Chen, Qi
Abstract: Antiphospholipid autoantibodies (aPLs), a major maternal risk factor for preeclampsia, are taken into the syncytiotrophoblast where they bind intracellular vesicles and mitochondria. Subsequently, large quantities of extracellular vesicles (EVs) extruded from syncytiotrophoblast into the maternal circulation are altered such that they cause maternal endothelial cell activation. However, the mechanism driving this change is unknown. First trimester placental explants were treated with aPL for 18 h. The EVs were then collected by different centrifugation. The levels of HSP 70, misfolded proteins, caspase 8 activity, and Mixed Lineage Kinase domain-Like (MLKL) were measured in placental explants and EVs. In addition, the levels of TNF-α and CD95 in conditioned medium were also measured. Treating placental explants with aPL caused an increase in levels of HSP 70, misfolded proteins and MLKL in placental explants and EVs. Increased activity of caspase 8 was also seen in placental explants. Higher levels of TNF-α were seen conditioned medium from aPL-treated placental explant cultures. aPLs appear to induce endoplasmic reticulum stress in the syncytiotrophoblast in a manner that involved caspase 8 and TNF-α. To avoid accumulation of the associated misfolded proteins and MLKL, the syncytiotrophoblast exports these potentially dangerous proteins in EVs. It is likely that the dangerous proteins that are loaded into placental EVs in preeclampsia contribute to dysfunction of the maternal cells.